Urban real-world driving traffic emissions during interruption and congestion. (March 2016) - Choudhary, Arti; Gokhale, Sharad
Graphical abstract: Highlights: Emphasis on interrupted and congested traffic-flows and concomitant emissions. Microscopic evaluation of operating conditions of test vehicles for emissions. Emission factors of different mileage vehicles for different traffic-flow patterns. Interrupted traffic-flow is highly emission-intensive due to several short events. Abstract: On-road emissions from urban traffic during interrupted and congested flow conditions are too high as compared to free-flow condition and often influenced by accelerating and decelerating speed due to frequent stop-and-go. In this study, we measured emissions from passenger cars and auto-rickshaws during peak and off-peak hours and analyzed according to different mileages with the instantaneous speed and acceleration for interrupted and congested traffic conditions. It was found that during flow, several short-events lasting over fractions of a second each lead to a sharp increase in pollutant emissions, indicating episodic conditions. The emission levels are sensitive to frequency and intensity of acceleration and deceleration, in accordance with the traffic-flow patterns and speed, besides mileages. Further, congestion conditions occur during both peak and off-peak hours, but last for different durations. The results are important in the sense that instantaneous estimates of pollutant emissions are necessary for the assessment of air quality in urban centers and for an effective traffic management plan.